A Report from the Pediatric Formulations Task Force: Perspectives on the State of Child-Friendly Oral Dosage Forms - Zajicek, Anne; Fossler, Michael J.; Barrett, Jeffrey S.; Worthington, Jeffrey H.; Ternik, Robert; Charkoftaki, Georgia; Lum, Susan; Breitkreutz, Joerg; Baltezor, Mike; Macheras, Panos; Khan, Mansoor; Agharkar, Shreeram; et al. (AAPS JOURNAL, 2013)
Despite the fact that a significant percentage of the population is unable to swallow tablets and capsules, these dosage forms continue to be the default standard. These oral formulations fail many patients, especially children, because of large tablet or capsule size, poor palatability, and lack of correct dosage strength. The clinical result is often lack of adherence and therapeutic failure. The American Association of Pharmaceutical Scientists formed a Pediatric Formulations Task Force, consisting of members with various areas of expertise including pediatrics, formulation development, clinical pharmacology, and regulatory science, in order to identify pediatric, manufacturing, and regulatory issues and areas of needed research and regulatory guidance. Dosage form and palatability standards for all pediatric ages, relative bioavailability requirements, and small batch manufacturing capabilities and creation of a viable economic model were identified as particular needs. This assessment is considered an important first step for a task force seeking creative approaches to providing more appropriate oral formulations for children.
Keywords: Children; Drugs; formulations; manufacturing; palatability; pediatrics; Regulatory